Meth Wars: Police, Media, Power - Linnemann, Travis (Alternative Criminology, 2016)
Frontmatter -- Contents -- Acknowledgments -- Introduction: The Methamphetamine Imaginary -- 1. Walter White’s Death Wish -- 2. This Is Your Race on Meth -- 3. Governing through Meth -- 4. The War Out There -- 5. Imagining Methland -- 6. Drug War, Terror War, Street Corner, Battlefield -- Notes -- References -- Index -- About the Author